Incumplimiento con la calidad adecuada en los procesos constructivos de obras de edificación, caso de estudio de centro comercial - Sobero Alania, Macario charles (2020)
This work focuses on quality improvement concerning the structural elements of a shopping center, in order to reduce and minimize the most relevant Non-Conformities that occurred on site. The project was based on the construction and expansion of tenants of a shopping center that will be rented as its purpose. By applying the Root Cause Analysis and using the Ishikawa diagram and Pareto diagram tools, it was possible to find the possible causes of quality noncompliance in the structural elements, which were subsequently validated in order to determine corrective actions. In the first chapter the problem statement, main and secondary problems, justification for the study, limitation and general and specific objectives are indicated. In the Second Chapter the theoretical framework is pointed out, where it mentions the quality in Peru, the total quality management, the costs of quality in construction, quality engineering and definitions. The third chapter indicates the use of Root Cause Analysis, the Cause Effect Diagram and Pareto Diagram tools. In the fourth chapter, the development of root cause analysis is presented using a sequence of steps. In the fifth chapter, The Economic Evaluation, Construction Budget, Repair Cost and Incurred Expense Analysis. Finally, in chapter six, the conclusions and recommendations of this work will be presented.